Models of consumer behavior of households depending on the income level - Melnikova A. S. (Science in figures, 2016)
the consumer behavior of households is defined by a complex of internal and external factors: income of the population, motives and incentives of behavior, behavioral norms and personal preferences. As the example of structure analysis of the income and expenses of households of Sverdlovsk region during research models of consumer behavior of households are allocated, characteristics and structure of the population depending on their welfare are allocated. Author's approach allows forecasting of the consumer market, proceeding from the socio-economic factors forming the level of the population income in the region.
Keywords: потребительское поведение; consumer behavior; домохозяйство; доходы и расходы населения; household; income and expenses of the population